Pattern of Patients in Intensive Care Unit in a Tertiary Care Hospital in Lumbini Province Nepal - Mandal, Rajesh Kumar; Bhandari, Nirajan; Gupta, Umang; Paudel, Sailes; Yadav, Krishna Kumar; Shakya, Nirmal (Nepal Mediciti Medical Journal, 2023)
BACKGROUND Intensive care is a crucial component of hospital care, reserved for patients with potentially recoverable conditions who can benefit from invasive treatment. However, in developing countries like Nepal, resources and availability of intensive care become hurdles in delivering healthcare. This study presents the pattern of admission and outcome of patients' management in a general intensive care unit (ICU) of this tertiary care center in Lumbini Province, Nepal. METHODS A cross sectional study conducted in the Department of Internal Medicine, Bheri Hospital between July 2021 to June 2022. A total of 792 patient’s details were obtained from the record section. Demographic data, diagnosis, duration of stay in ICU, managing units, and outcome were collected and analyzed with Statistical Package for the Social Sciences 20. RESULTS A total of 729 patients were admitted in the study period; 57.82% were male and 42.18% were female. Majority 60% of admissions were from Department of Medicine followed by Cardiology 24% and Surgery 10%. Pneumonia and Chronic Obstructive Pulmonary Disease 18.30% followed by Myocardial Infraction 14.52%, Acute abdomen 10.22% and sepsis 9.84% were the most common morbidity. Mean duration of ICU stay was 3.5. days. Discharge rate was 69.82% and the mortality rate was 17.80 %. CONCLUSION The most common patients admitted in the ICU of Bheri hospital were mostly Medical cases. Surgical and obstetric cases were lesser in number. The outcomes were comparable with other multidisciplinary ICU of similar settings.